Critique of ‘Management of post-traumatic retained hemothorax: A prospective, observational, multicenter AAST study’ - Rahma Salim; Mazin A. Tuma; Rifat Latifi; Hassan Al Thani (Journal of Emergency Medicine, Trauma and Acute Care, 2012)
Background:The natural history and optimal management of retained hemothorax (RH) after chest tube placement is unknown. The intent of our study was to determine practice patterns used and identify independent predictors of the need for thoracotomy. Methods: An American Association for the Surgery of Trauma multicenter prospective observational trial was conducted, enrolling patients with placement of chest tube within 24 h of trauma admission and RH on subsequent computed tomography of the chest. Demographics, interventions, and outcomes were analyzed. Logistic regression analysis was used to identify the independent predictors of successful intervention for each of the management choices chosen and complications. Conclusion:RH in trauma is associated with high rates of empyema and pneumonia. VATS can be performed with high success rates, although optimal timing is unknown. Approximately, 25% of patients require at least two procedures to effectively clear RH or subsequent pleural space infections and 20.4% require thoracotomy.